2021
DOI: 10.1038/s41598-021-89355-5
|View full text |Cite
|
Sign up to set email alerts
|

Blocking facial mimicry during binocular rivalry modulates visual awareness of faces with a neutral expression

Abstract: Several previous studies have interfered with the observer’s facial mimicry during a variety of facial expression recognition tasks providing evidence in favor of the role of facial mimicry and sensorimotor activity in emotion processing. In this theoretical context, a particularly intriguing facet has been neglected, namely whether blocking facial mimicry modulates conscious perception of facial expressions of emotions. To address this issue, we used a binocular rivalry paradigm, in which two dissimilar stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 86 publications
3
16
0
Order By: Relevance
“…Particularly, manipulation of body posture or hand posture was found to modulate tactile perception (Longo, 2017 ) and visual perception of size (Kim et al, 2021 ), letters (Barnett-Cowan et al, 2015 ) and faces (Barnett-Cowan et al, 2015 ; Davidenko & Flusberg, 2012 ). In the domain of face perception, previous research has focused on the effect of somatosensory stimulation (via enforced face pose or brain stimulation) on emotion recognition (Borgomaneri et al, 2020 ; Niedenthal, 2007 ; Oberman et al, 2007 ; Quettier et al, 2021 ). Across these studies, a reduced emotion recognition ability was identified when participants could not mimic facial expression, or when a TMS was delivered to their somatosensory cortex (Pitcher et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, manipulation of body posture or hand posture was found to modulate tactile perception (Longo, 2017 ) and visual perception of size (Kim et al, 2021 ), letters (Barnett-Cowan et al, 2015 ) and faces (Barnett-Cowan et al, 2015 ; Davidenko & Flusberg, 2012 ). In the domain of face perception, previous research has focused on the effect of somatosensory stimulation (via enforced face pose or brain stimulation) on emotion recognition (Borgomaneri et al, 2020 ; Niedenthal, 2007 ; Oberman et al, 2007 ; Quettier et al, 2021 ). Across these studies, a reduced emotion recognition ability was identified when participants could not mimic facial expression, or when a TMS was delivered to their somatosensory cortex (Pitcher et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…To note, differently from the continuous flash suppression paradigm, for instance implemented in Korb et al (2017), BR allows to monitor modulations of both access and stabilization in consciousness of facial expressions. Indeed, psychological processes involved during the BR have been previously characterized considering three measures (Quettier et al, 2021). First, the initial percept (IP) is defined as the first dominant rivaling stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we specifically hypothesize that recruiting somatosensory representations will facilitate conscious experiencing of happy facial expressions, in terms of conscious stabilization (i.e., dominance, CT) over neutral facial expressions. The main reason for this choice derives from the results of our previous study (Quettier et al, 2021), in which the participants' facial mimicry was manipulated during a task similar to the one planned here. The results highlighted that this type of manipulation has an impact on the conscious processing of facial expressions during the stabilization phase of the content in consciousness (as indicated by the modulation of the cumulative time as a function of the mimicry manipulation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulations of facial mimicry have been shown to influence a wide range of abilities, including perception and categorization of other people's facial expressions (Lewis & Dunn, 2017;Quettier et al, 2021;Wood et al, 2016a); representations of facial expressions in visual working memory (Sessa et al, 2018), or semantic processing of emotional language (Davis et al, 2015). In addition, interfering with facial movements changes neural responses to emotion expressions.…”
Section: Introductionmentioning
confidence: 99%